Evaluating the Efficiency of a Trace Amount of Zr Dopant on Photocatalytic Activity of TiO2 in Decolorization of Azo Dye - Tania Bigdeli; Shahram Moradi Dehaghi (Emerging Science Journal, 2018)
Zr-doped TiO2 nano photocatalyst obtained with a various trace amount of Zr, by using the sol-gel method. Several spectroscopic techniques applied to characterize the structures and properties of nano-photocatalyst. It founded that the effect of doping Zr ions to the TiO2 lattice led it to improve the surface properties and decreasing the particle size of nano-photocatalyst. Therefore, it causes increasing specific surface area and photocatalytic activity as compared with pure TiO2. The results revealed that there was an inverse relationship between the growth of the crystallite size of the nano photocatalyst and the decline of the molar ratios of Zr. The photocatalytic activity of the nano photocatalyst employed for the decolorization of Congo red as an Azo dye in the aqueous solution under UV irradiation in a batch reactor. The results exhibited that the TiO2/Zr0.0004 brings the best photocatalytic activity.